Proposed Improvements in The Management of Organizational Culture Change (A Case Study at Yayasan XYZ Bandung) (The Indonesian Journal of Business Administration, 2015)
Abstract. Yayasan XYZ is an International Non-Profit Organization that specializes in children development through sponsorship, dedicated to releasing children from poverty. The culture and value system play a major role in how an organization reacts to change and organization members are more inclined to embrace change when the organization’s culture is aligned with the mission and goals of the organization.  One of the approaches in managing organizational change is using Kotter’s 8-Step Change Model. By following the 8 Step Process outlined by Professor Kotter, organizations can avoid failure and become adept at change. Organizations can increase their chances of success, both today and in the future by improving their ability to change. The author analyze how to implement the desired culture relate to values in the organization. All analyses and solutions use Organizational Change method and 7-S McKinsey. Based on the analysis and recommendation of solutions, Yayasan XYZ must prioritize the development to the style, staff, skills, system and work strategy in accordance with the organization’s existing values. Another recommendation on the approaches to managing organizational change, especially in Yayasan XYZ should be using both Kotter’s 8-Step Model and Organizational Development (OD). Keywords: change management, organizational culture, 7-S, Kotter’s 8-Step change model